Consumer Happiness in the Purchase of Electric Vehicles: a Fuzzy Logic Model - Lámbarry-Vilchis, Fernando; Barsekh Onji, Aboud; Chavarría López, Leticia Refugio; Maldonado Colín, Paola Judith (Mercados y Negocios, 2025)
This study analyzes customer happiness in acquiring an electric vehicle, considering pleasure as an ambiguous language term that conventional models have inadequately incorporated. This research was conducted using a fuzzy Delphi method survey targeting a specific consumer group and two fuzzy inference systems: a multi-input single-output FIS model and an FIS Tree employing a hierarchical fuzzy inference structure, which leverages the survey's training data to optimize the models using different machine learning algorithms. The FIS tree model demonstrated superior efficacy in predicting the consumer satisfaction index, achieving an average forecast error of 0.65%. This approach could assist automobile agency marketers in creating accurate predictions to evaluate the purchasing decision-making process.